Collaborative planning in the new media age: The Dafo Temple controversy, China. (June 2015) - Deng, Zhaohua; Lin, Yanliu; Zhao, Miaoxi; Wang, Shifu
Highlight: New media generates new types of collaborative planning with more diverse agents, more flexible communication, and newer roles of planners; but challenges lie in digital divide, procedural management, and spatial deliberation. Abstract: New media have accelerated China's social transition by distributing information, restructuring ways of communication, and changing social relationships and public values. They have also facilitated the development of new types of collaborative planning that are characterized by a broad range of agents, new forms of communication, and new roles for planners. These new types of collaborative approaches promote social interaction, public participation, and the collaboration between various actors. By reviewing theoretical and empirical studies, this article first presents a conceptual framework for assessing collaborative planning in the new media age. The framework comprises three components: the diversity of agents, the nature of communication, and the roles of planners. A case study of the Dafo Temple controversy is used to illustrate the framework's application. After comparing traditional with new forms of collaborative planning, ways to achieve effective consensus building in collaborative planning in the new media age are suggested.